Traditionalist aspect of sociocultural practices: historical memory in the conditions of information war - Григорій Ковальський (Cхід)
The article aims to study the role of philosophical traditionalist concepts in socio-cultural practices and the development of historical memory. Historical memory is proven to be a tool for transferring social experience, as well as scientific and non-scientific knowledge about the shared past and an entire system of self-identification of society. At the same time, historical memory is a dimension of the individual and collective memory of the historical past, representing it from a symbolic perspective. As a sociocultural phenomenon, historical memory accumulates a set of images and collective perceptions, reproducing the community's cultural and historical experience. The nature of society implies that previous socio-historical stages are causally related to the present. The current historical period forms the basis of the future. The connection of the present with the past is the basis of tradition. Cognition of traditional symbols is performed with the help of a particular "symbolic method" of analogies. The superhuman in tradition is revealed in the direct experience of the sacred, after which the transcendental realm begins. Attributing to tradition a metaphysical, not just socio-cultural status, traditionalists are guided by the existential integrity of human existence in the system of the tradition, the interconnection of all its manifestations, and the connection between the revealed and unrevealed levels of reality.